Discrete element modeling of continental deformation and volcanic spine extrusion - Jiao, Liqing (2016)
The India-Asia collision zone is an example of the largest present day continental deformation, which started about 55 Ma ago. Previous unscaled 2D modeling of such deformation did not address either the growth of topographic relief or localized faulting. Here, we use the YADE Discrete Element Method (DEM) code to produce a suite of scaled 3D models of the collision. They generate two plate-scale strike-slip faults that extrude and rotate large coherent blocks. The locations, lengths, ages and offsets of the model faults are in keeping with those of the Red River and Altyn Tagh mega faults, east and north of Tibet. The model also generates plateaus similar to Tibet.